Krisis Identitas Perempuan dalam Bab “The Problem That Has No Name” pada Buku The Feminine Mystique Karya Betty Friedan dalam Perspektif Al-Qur'an - Arya Pandji Pratama; Rakha Muhammad Hafizh; Adya Abiyyu Dharma; Nabila Sadida; Dadan Firdaus (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze women's identity crisis in the chapter The Problem That Has No Name by Betty Friedan using Erik Erikson's theory and a Qur'anic perspective. This qualitative study employed library research and content analysis methods. The findings reveal that women experience loss of self-identity, self-doubt, and difficulties in finding meaning in life. The crisis is influenced by social factors, limited opportunities for self-development, and pressures of feminine ideals. From a Qur'anic perspective, QS. An-Nahl [16]: 97 and QS. An-Nisa' [4]: 32 emphasize the importance of self-development and recognition of individual efforts.